Learning Style and Preferences of Students in Skills-Based Courses - Ann Gladys G. Delos Angeles, Marie (International Journal of Psychosocial Rehabilitation, 2020)
When teachers teach students with consideration of their preferred learning styles and recognize their unique qualities, then teachers are making a commitment to providing tools and opportunities needed for students to achieve success. The study was conducted to determine the preferred learning style of students enrolled in the skills-based courses of a state university in Cagayan Valley, Philippines. Differences in the preferred learning style across sex, courses, curriculum year, and GWA of the 480 students enrolled in four (4) undergraduate technology-based courses were described through the use of Computerized Assessment Program- Styles of Learning (CAPSOL). Results showed the learning style preferred include individual, written expression, sequential, and bodily-kinesthetic. When grouped according to sex, course, curriculum year and GWA, females are bodilykinesthetic and individual learners, while, males show preference to visual-auditory and group learning. Among the four courses, students taking Accounting Technology are visual learners while those from the other courses were bodily-kinesthetic. Students in their sophomore year show preference to being sequential learners. In terms of GWA, those with lower tend to learn new materials with a group and those with higher prefer to study alone. Since differences in preferred learning styles were found, there is a need to expose students to varied learning tasks where they are best engaged and offer instructional materials responsive to their needs and learning styles.